Social Media And Word Of Mouth Effects On Buying Decision Process On Janji Jiwa Coffee In East Jakarta - Nicolas Nicolas; Hari Susanta Nugraha; Andi Wijayanto (Syntax Literate, 2023)
This research aimed to analyze Consumer behavior of Janji Jiwa coffee which focuses on the buying decision process from consumers, which includes the influence of Instagram promotion and word of mouth on buying decisions, which mediated by purchase intention and brand awareness from Kopi Janji Jiwa in East Jakarta. This Research survey was conducted through Questionnaire on 100 Janji Jiwa customers who have bought the Janji Jiwa coffee at least 4 times in Janji Jiwa outlets in AEON mall Jakarta Garden City and Transera Waterpark at East Jakarta. All the responses are processed with path analysis using Smart - PLS application. The results finding reveal that between Instagram promotion (Advertising) and word of mouth, Purchase Intention and Brand Awareness, and Buying decision, each of these variables has an effect on each other. But there are no influence between word of mouth on purchase intention. In Addition, Purchase intention and brand awareness are proven to mediate and strengthen the relationship between Instagram promotion and word of mouth towards buying decision. Also, Brand Awareness is proven to mediate and strenghten the relationship between word of mouth towards purchase intention